The impact of the European Youth Guarantee on active labour market policies: A convergence analysis - Tosun, Jale; Treib, Oliver; De Francesco, Fabrizio (International journal of social welfare, 2019)
The European Union’s (EU) Youth Guarantee aims to improve the labour market situation of young people. Rather than prescribing a uniform policy model, it acknowledges that supportive measures need to align with national, regional and local circumstances. It thus seeks to promote mutual policy learning through the open method of coordination. As an innovative measure, the EU has deployed funding programmes to support the domestic measures related to the Youth Guarantee. We therefore examined in this study whether this mix of recommendations and financial incentives has entailed a convergence of member state policies. Our analysis of policy outputs for the period 2007−2014 yields a mixed empirical picture. There is catching-up convergence regarding policies’ sectoral coverage but increasing divergence concerning the number of adopted policy instruments. The first two years of financial incentives did not produce any effect on enhancing policy experimentation among less active member states. We offer an optimistic and a pessimistic interpretation of these findings.